Lipid-coated iron oxide nanoparticles for dual-modal imaging of hepatocellular carcinoma - Liang J (Dove Medical Press, 2017)
Jinying Liang,1–3 Xinxin Zhang,2 Yunqiu Miao,2 Juan Li,1 Yong Gan2 1Department of Pharmaceutics, China Pharmaceutical University, Nanjing, People’s Republic of China; 2Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, People’s Republic of China; 3School of Pharmacy, Xinxiang Medical University, Xinxiang, People’s Republic of China Abstract: The development of noninvasive imaging techniques for the accurate diagnosis of progressive hepatocellular carcinoma (HCC) is of great clinical significance and has always been desired. Herein, a hepatocellular carcinoma cell-targeting fluorescent magnetic nanoparticle (NP) was obtained by conjugating near-infrared fluorescence to the surface of Fe3O4 (NIRF-Fe3O4) NPs, followed by coating the lipids consisting of tumoral hepatocytes-targeting polymer (Gal-P123). This magnetic NP (GPC@NIRF-Fe3O4) with superparamagnetic behavior showed high stability and safety in physiological conditions. In addition, GPC@NIRF-Fe3O4 achieved more specific uptake of human liver cancer cells than free Fe3O4 NPs. Importantly, with superparamagnetic iron oxide and strong NIR absorbance, GPC@NIRF-Fe3O4 NPs demonstrate prominent tumor-contrasted imaging performance both on fluorescent and T2-weighted magnetic resonance (MR) imaging modalities in a living body. The relative MR signal enhancement of GPC@NIRF-Fe3O4 NPs achieved 5.4-fold improvement compared with NIR-Fe3O4 NPs. Therefore, GPC@NIRF-Fe3O4 NPs may be potentially used as a candidate for dual-modal imaging of tumors with information covalidated and directly compared by combining fluorescence and MR imaging. Keywords: dual-imaging, magnetic resonance imaging, hepatocellular carcinoma, tumor-targeting